Impelementasi Knowledge Management Pada UKM Sentra Pengrajin Sepatu di Desa Kotabatu Ciomas Kabupaten Bogor - Sefrika Entas (Universitas Bina Sarana Informatika, 2017)
Small and medium enterprises is one pillar of the people's economy. Bogor Regency has several centers of small businesses spread across several regions. Kotabatu village is famous as a center for local shoe craftsman whose products are distributed to various regions in Indonesia. But the craftsmen still have problems in marketing and managing their business. To support the advancement of the business, it needs a good strategy so that business goals are achieved. Knowledge management applications can help the craftsmen to carry out an integrated and comprehensive approach to policy making and strategic steps for business continuity and business. Keyword: knowledge management, Kotabatu craftsmen shoes, Kabupaten Bogor